Layered/spinel heterostructured Li-rich materials synthesized by a one-step solvothermal strategy with enhanced electrochemical performance for Li-ion batteries. Issue 1 (1st December 2015) - Deng, Ya-Ping; Fu, Fang; Wu, Zhen-Guo; Yin, Zu-Wei; Zhang, Tao; Li, Jun-Tao; Huang, Ling; Sun, Shi-Gang
Abstract : Li-rich materials, Li1.140 Mn0.622 Ni0.114 Co0.124 O2, of a layered/spinel heterostructure were synthesized by a one-step solvothermal route with subsequent moderate heat treatment. Abstract : Li-rich materials, Li1.140 Mn0.622 Ni0.114 Co0.124 O2, of a layered/spinel heterostructure were synthesized by a one-step solvothermal route with subsequent moderate heat treatment. The as-prepared materials consist of hierarchical microspheres and an integral layered/spinel heterostructure. The effects of calcination time on both the structure and electrochemical performance of materials have been studied systematically. It has been found that the formation of the spinel structure could be controlled by adjusting the calcination time at 650 °C, and the materials calcined at this temperature for 24 hours present the optimal electrochemical performance. High initial efficiencies of 101% at 0.2C and 92% at 2C, as well as high discharge capacities of 280, 256, 234 and 206 mA h g −1 respectively at 1C, 2C, 5C and 10C have been achieved. The empty 16c octahedral site and 3D Li + diffusion channel provided by the spinel have been regarded as the key to the improvement of electrochemical performances.